ANALISIS STATISTIKA PERKEMBANGAN TAHFIDZ MAHASISWA PRODI BAHASA DAN SASTRA INDONESIA FKIP UMT BERDASARKAN LAPORAN AIK PEKAN 84-88 - rukmono (Program Studi Pendidikan Matematika, Universitas Muhammadiyah Kupang, 2024)
Abstract This paper tells about analysis statistics of tahfidz program for students of Indonesian Language and Literature Study Program (PBSI) Universitas Muhammadiyah Tangerang. This research use data prepared by AIK Board UMT which is responsibilitiy of tahfidz program UMT. Based on the data, we intepretating that data into graphic so that we can see the progress of tahfidz program. Using the same data we did statistics analysis as percentage tahfidz progress from 84th untik 88th weeks for every single week. Background why we took this research is because we need something that we can see the progress of tahfidz program. The reason why we took our object research are students from PBSI because thay are disciplines and consistance to this program. The result of this research can be used by AIK as a report to make decision to better forward. Method that we use is quantative statistics which give a result that the progress of tahfidz program likely 0%, 14,28%, 28,57%,42,85%, 57,14%, 71,42%, 85,71% and 100% . Percentage 0 % meaning that students did not use even one day in a week to record they tahfidz remembering. Pecentage 100% meaning that students fully 7 days in a week to record they tahfizd. More over each percentage 14,28%, 28,57%,42,85%, 57,14%, 71,42%, 85,71% meaning that students used 1,2,3,4,5 and 6 days to record they tahfidz. For furthur information about the name of the students with they own tahfidz percentage progres or for the complete result can be seen in this paper chapter discussion and result bellow. Keywords: Analysisi, Statistics, Tahfidz, Students, PBSI